Perioperative changes in hemoglobin levels during major hepatopancreatic surgery in transfused and non-transfused patients. (September 2021) - Lammi, J.P.; Eskelinen, Matti; Tuimala, Jarno; Selander, Tuomas; Saarnio, Juha; Rantanen, Tuomo
Background: Several studies have shown that restrictive transfusion policies are safe. However, in clinical practice, transfusion policies seem to be inappropriate. In order to assist in decision-making concerning red blood cell transfusions, we determined perioperative hemoglobin (Hb) levels during major pancreatic and hepatic operations. Methods: Patients who underwent major pancreatic or hepatic resections between 2002 and 2011 were classified into the transfused (TF+) and non-transfused (TF) groups. The perioperative Hb values of these patients were evaluated at six points in time. Results: The study included 1596 patients, of which 785 underwent pancreatoduodenectomy, 79 total pancreatectomy, and 732 partial hepatectomy. Similar perioperative changes in Hb levels were seen in all patients regardless of whether they received a blood transfusion. In patients undergoing pancreatoduodenectomy and total pancreatectomy, the median of the lowest measured hemoglobin values was 89.2 g/L and in partial hepatectomy patients 92.6 g/L, and these were assumed to be the trigger points for red blood cell transfusion. Conclusions: Despite guidelines on blood transfusion thresholds, restrictive blood transfusion policies were not observed during our study period. After major pancreatic and hepatic surgery, Hb levels recovered without transfusions. This should encourage clinicians to obey the restrictive blood transfusion policies after major hepatopancreatic surgery.